Impact of low anterior resection syndrome (LARS) on the quality of life and treatment options of LARS – A cross sectional study. (February 2021) - Pape, E.; Pattyn, P.; Van Hecke, A.; Somers, N.; Van de Putte, D.; Ceelen, W.; Van Daele, E.; Willaert, W.; Geboes, K.; Van Nieuwenhove, Y.
Abstract: Purpose: The purpose of this study was to assess the relationship between the low anterior resection syndrome (LARS) and quality of life (QOL). Furthermore, in patients with major LARS, therapeutic management options were explored. Methods: A cohort of surviving patients, who underwent a low anterior resection for rectal cancer after long course of radiochemotherapy, were identified. These patients were treated in Ghent University Hospital between 2006 and 2016. QOL was assessed using the European Organization for Research and Treatment of Cancer Quality Of Life questionnaire-C30 and the bowel function using the LARS-score. The relationship between LARS and QOL was analysed. Patients with major LARS (≥30 points) were contacted to explore their therapeutic management of LARS. Results: 69% of the participants had major LARS. QOL was closely associated with LARS. Significant differences were found between those with and without LARS in the global health status (p ≤ 0.001) and in the following functional scales: physical (p ≤ 0.001), role (p ≤ 0.001), cognitive (p = 0.04) and social (p ≤ 0.001). Patients with major LARS experienced more diarrhea (p ≤ 0.001), fatigue (p = 0.002), insomnia (p ≤ 0.001) and pain (p = 0.02), compared to patient with no/minor LARS. Most patients tried dietary regimens (71%), medication (71%) and incontinence material (63.8%) in an attempt to manage their LARS and found some of them useful. The level of the anastomosis (low) was a significant risk factor for major LARS (p=0.03). Conclusion: More than half of the patients in this cohort still suffered from major LARS. Patients confronted with major LARS had a lower QOL than patients with no/minor LARS. Currently, there is no gold standard for the management of LARS. Patients manage it through trial and error.